1994
DOI: 10.1063/1.555953
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluated Kinetic Data for Combustion Modeling. Supplement I

Abstract: This compilation updates and expands a previous evaluation of kinetic data on elementary, homogeneous, gas phase reactions of neutral species involved in combustion systems [J. Phys. Chem. Ref. Data 21, 411 (1992)]. The work has been carried out under the auspices of the European Community Energy Research and Development Program. Data sheets are presented for some 78 reactions and two tables in which preferred rate parameters are presented for reactions of ethyl, i-propyl, t-butyl, and allyl radicals are given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
357
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(398 citation statements)
references
References 1 publication
38
357
0
3
Order By: Relevance
“…5,6 electronic states for higher temperature is minor. The forward rate coefficients from this work have been validated against theoretical results from previous works [15][16][17] and the present ansatz provides a generic computational framework for obtaining such data from computation. …”
mentioning
confidence: 62%
See 1 more Smart Citation
“…5,6 electronic states for higher temperature is minor. The forward rate coefficients from this work have been validated against theoretical results from previous works [15][16][17] and the present ansatz provides a generic computational framework for obtaining such data from computation. …”
mentioning
confidence: 62%
“…(8) with parameters A = 6.87 × 10 8 cm 3 s −1 mol −1 K −n , E a = 1.9 × 10 4 kcal/mol, and n = 1.13. 16 Bose et al reported rate coefficients k − (T) for the reverse reaction based on QCT on the 2 A ′ and 4 A ′ PESs for temperatures ranging from 1000 to 14 000 K. 17 In order to obtain the forward reaction rate coefficients using Eq. (1), these data were combined with CEA data 5,6 for the equilibrium rates K(T) (available from 300-20 000 K).…”
mentioning
confidence: 99%
“…For comparison, H + ethylene has E a ≈ 9 kJ mol -1 in the high-pressure limit at 298 K. 18 The computational results in Table 2 confirm the presence of significant barriers along both H-atom addition pathways.…”
Section: Discussionsupporting
confidence: 61%
“…Gas-phase reactions may be ignored since H 2 O molecules are unreactive to radical species at moderate temperatures. Thermal decomposition of H 2 O in the gas phase is slow [27]. Reactions between radical species in the gas phase can be ignored because of their low densities.…”
Section: Discussionmentioning
confidence: 99%